Ketimpangan Sosial, Konflik Agama, dan Persoalan Patriarki dalam Novel Al-Mutawali As-Salih Karya Wadi’ Abu Fadil: Kajian Realisme Sosialis - Arina Zakiah Azzahra; Misbahus Surur (Universitas Lambung Mangkurat, 2026)
Wadi’ Abu Fadil’s novel Al-Mutawali As-Salih portrays Lebanese social realities, particularly interreligious conflict and structural gender inequality. This study fills the gap in previous studies, which mostly focused on psychological and interpersonal aspects, by examining structural social inequalities through socialist realism. Using a descriptive, qualitative method and close-reading techniques, the data were analyzed using Miles and Huberman’s interactive model. The analysis applies socialist realism as the primary framework, supported by theories of power and patriarchy from Georg Lukács, Friedrich Engels, Pierre Bourdieu, and Deniz Kandiyoti. The findings reveal: (1) ideological tensions between Islam and Christianity, (2) spatial and educational restrictions on women, and (3) the normalization of patriarchal authority within family and social structures. The novel thus functions as a literary articulation of systemic inequality rather than merely a narrative of individual conflict. This study contributes to Arabic literary criticism by offering a structurally grounded interpretation of the novel within a socialist realist perspective.